The Future of Supplier Selection: Integrating Bibliometric Intelligence and MCDM in The Perishable Agro-Industry - Dwi Iryaning Handayani; Kurnia Iswardani; Misra Hartati; Muhamad Zulkiflee Osman; Mimik Umi Zuhroh (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Supplier selection in the perishable agroindustry, such as for mushrooms, is a complex and strategic process. It significantly impacts supply chain performance owing to the perishability and quality sensitivity of the products involved. Traditionally, decision-making methods in this area often lack preliminary validation, resulting in suboptimal supplier choice.Purpose: This study aims to integrate bibliometric analysis and multi-criteria decision-making (MCDM) approaches, particularly the Analytic Hierarchy Process (AHP), to develop a robust data-driven model for supplier selection in the mushroom agroindustry.Design/methodology/approach: A systematic literature review using the PRISMA framework and bibliometric analysis of Scopus-indexed articles identified the most relevant MCDM methods. A case study approach involving expert judgment was used to evaluate mushroom suppliers based on the following five criteria: quality, price, delivery, service, and product suitability.Findings/Result: A bibliometric review confirmed that AHP, TOPSIS, and fuzzy logic are the most frequently applied methods. AHP was selected for its strengths in handling both qualitative and quantitative data and validating decision consistency. The results showed that Supplier A had the highest overall score (0.389), followed by Supplier C (0.345) and Supplier B (0.266), with a consistency ratio (CR) below 0.10, validating the assessments.Conclusion: Integrating bibliometric analysis with MCDM methods offers a more objective and evidence-based approach to supplier selection. The developed model enhances decision accuracy, supports strategic sourcing, and ensures quality and timeliness in highly perishable product supply chains.Originality/value (State of the art): This study pioneers the direct integration of bibliometric insights into an MCDM-based decision-making framework applied in a real-world agroindustry context. The methodology is replicable and adaptable across various industries facing similar supplier evaluation challenges. Keywords: supplier selection, multi-criteria decision making, analytic hierarchy process, bibliometrics